2016
DOI: 10.1111/epi.13517
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying antiepileptic drug effects using intrinsic excitability measures

Abstract: Pathologic increases in excitability levels of cortical tissue commonly underlie the initiation and spread of seizure activity in patients with epilepsy. By reducing the excitability levels in neural tissue, antiepileptic drug (AED) pharmacotherapy aims to reduce seizure severity and frequency. However, AEDs may also bring about adverse effects, which have been reported to increase with higher AED load. Measures that monitor the dose-dependent effects of AEDs on cortical tissue and quantify its excitability le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Many of the patients in our study underwent antiepileptic medication reduction as part of presurgical monitoring, making it difficult to disentangle the effects of changing drug levels from other potential slow-varying modulators of seizure pathways. Changes in antiepileptic medication can impact neural excitability (68)(69)(70), and medication tapering increases seizure likelihood in most patients (16,71); however, it is controversial whether it also affects seizure patterns (9,16,56,71). In some cases, it appears that medication tapering reveals latent seizure pathways that are suppressed by medication (9) or allows existing pathways to further progress (e.g., the secondary generalization of typically focal seizures) (16).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the patients in our study underwent antiepileptic medication reduction as part of presurgical monitoring, making it difficult to disentangle the effects of changing drug levels from other potential slow-varying modulators of seizure pathways. Changes in antiepileptic medication can impact neural excitability (68)(69)(70), and medication tapering increases seizure likelihood in most patients (16,71); however, it is controversial whether it also affects seizure patterns (9,16,56,71). In some cases, it appears that medication tapering reveals latent seizure pathways that are suppressed by medication (9) or allows existing pathways to further progress (e.g., the secondary generalization of typically focal seizures) (16).…”
Section: Discussionmentioning
confidence: 99%
“…Our demonstration of scale-invariant size distributions suggests avalanche dynamics are maintained throughout task performance, which should mirror a sustained average synchrony among cortical sites. Previous studies have shown overall phase-synchronization between sites sensitively captures fast dynamical changes in a network ( Kitzbichler et al, 2009 ; Yang et al, 2012 ), in particular at higher frequencies ( Meisel et al, 2016 ). In line with our results from adaptive binning and thresholding, levels of LFP synchrony R (see Materials and methods) were not different across epochs in monkey A (Left: 0.56 ± 0.015, 0.56 ± 0.01 and 0.56 ± 0.01; Right: 0.56 ± 0.01, 0.55 ± 0.01 and 0.56 ± 0.004; mean ± standard deviation for BASE, EARLY and LATE respectively; p>0.05; two-tailed paired student’s t-test) as well as in monkey B (BASE, 0.450 ± 0.003; mean ± standard deviation; vs. PRE, 0.452 ± 0.003; vs. POST, 0.455 ± 0.003; p>0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Data driven modeling may provide the opportunity to identify which drug could be helpful for different classes of seizure, as different mechanisms of anti-epileptic drug action may preferentially effect the various connectivity parameters, though further validation of model predictions is needed to translate estimation results to clinical practice. Levels of AEDs have been related to features of the EEG signal [ 59 , 60 ]. Therefore, it may be possible to extend this relationship to predicting the mode of action of an AED from an individual’s EEG.…”
Section: Discussionmentioning
confidence: 99%